Study Analytical of The Effect Magnesium ion Concentration to Determination the Total Hardness And Comparison Spectrophotometry - Baghdad Science Journal (مجلة بغداد للعلوم)
The determination hardness in water raised to rivers caused several problem in the validity of the water used depends on where determination ions concentration calcium and magnesium in salts carbonate and sulfate , this possibility of separation between of these ions and the resulting impact on concentration and determination the degree of hardness water and appreciation between the insolvent water quality . It study the effect of the impact of concentration magnesium ion in determination the quality of the water has turned out to be Mg concentration more than 60% of the total content of hardness is borderline in hardness effect the determination. Adopted in this research determination the ions in two method titration by EDTA solution and using indicators Murexide ,Erochrom Black T and comparison the results by used spectrophotometer method Atomic absorbance method (AAS) . The results showed the accuracy of the colorimetric method by titration chemistry more than spectrophotometer method and magnesium ion maximum effect when present in higher concentration have an effect on the quality and specification of the water and made it change the degree of hardness to another